Development of Digital Controller for DC-DC Buck Converter - Sarun Soman; Sangeetha T.S. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents a design & implementation of 3P3Z (3-pole 3-zero) digital controller based on DSC (Digital Signal Controller) for low voltage synchronous Buck Converter. The proposed control involves one voltage control loop. Analog Type-3 controller is designed for Buck Converter using standard frequency response techniques.Type-3 analog controller transforms to 3P3Z controller in discrete domain.Matlab/Simulink model of the Buck Converter with digital controller is developed. Simualtion results for steady state response and load transient response is tested using the model.